Wake Up and Live: The Roots of Cosmopolitanism in Oriental Worldview - Reza A. A. Wattimena (Jurnal Ilmiah Hubungan Internasional, 2017)
This article describes the roots of cosmopolitanism in Oriental worldview, especially in the Indian and Chinese worldview. The idea of cosmopolitanism is important to understand today. It is seen as an alternative solution for various conflicts with religious and cultural motives as background. Oriental civilizations developed the idea of cosmopolitanism through various philosophical teachings, such as Vedanta and Buddhism. Both of them are inherently meditative and cosmopolitan. They focus on insight on reality as it is, not reality as it is conceptualized by religion, philosophy or science. This insight deconstructs also the normal understanding of self-identity and stimulates the rise of cosmopolitan awareness, which is inherently experiential. Without this experience and awareness, various theoretical reflections on cosmopolitanism will be useless.